THE PENDHOK STYLE OFSURAKARTA KRIS A CASE STUDY OF DHONI KUSTANTO AS PENDHOKARTIST OF 90S MRANGGI GENERATIONS - G., Guntur (Proceeding IICACS, 2019)
Kris(keris) is a kind of Javanese dagger with its main parts: blade, hilt, sheath, andpendhok.The pendhok is a protective part of the sheath, usually made of various metals such as silver, bronze, copper, brass, and even gold. Krisof tangguh nom (young period) which later specified as tangguh Surakarta (Surakarta period) becomes a model in the making ofpendhok. Tangguh (period) means an identification of kris based on the period of kingdoms with its empu (kris masters). The formation of pendhok inSurakarta style means connected with the form of Surakarta kris which conceptualized by PB III to differentiate with Kasunanan Kartasura. The tangguh Surakarta isaccepted as a style of kris which has aform of distinction to the another kingdom: Yogyakarta. Seemingly the aesthetic ofpendhok and Surakarta kris is remained the original post-Kartasura trace but with the authenticity of PB III. The form of Surakarta kris is recognizable by the shape of sheath (warangka), especially ladrang and gayaman, with the hilt of tunggak semi (spring stump). The pendhok form follows the sheath style, and its ornaments mostly signify an adopted art of pre-Islam: Hindu – Budha. As Majapahit diminishes and Islam arose, the kris then shaped in the palace traditions in the hegemony of Islam Kejawen and the king is in the center. Kris culture arranged as a form of synthesis between Old Java of Majapahit with the New Java of Islam Pesisiran (seashore) in the era of Islamic Mataram by Sultan Agung. During the colonialism, the conflict over Mataram authority hadchangedJava, alsomade Surakarta and its kris form producedin different identities through the kris culture and customary fashion in the Palace and then rooted in the Surakarta folk by the mranggi in the outside of Palace.Keywords: pendhok, Mranggi, Ornament, Kris, Folkart, Identity, Surakarta, Java